Extraction and characterization of humus with reference to clay-associated humus - Anderson, D. W., author; Paul, E. A., author; St. Arnaud, R. J., author; Agricultural Institute of Canada, publisher (Colorado State University. Libraries, 1974)
An extraction-fractionation method was developed with which it is possible to isolate 60–67% of the humus of Chernozemic and Luvisolic soils. Two humic acid fractions were obtained: (1) a conventional alkali-pyrophosphate extractable HA-A; (2) a clay-associated HA-B fraction isolated after ultrasonic dispersion, in water, of the residue of the alkali-pyrophosphate extraction. As compared to the HA-A, the HA-B fractions had lower C contents but greater N contents, narrower C:H ratios, higher molecular weights, and less resistance to hydrolysis in 6 N HCl. It was concluded that the HA-B is a weakly humified, potentially labile humic constituent stabilized by adsorption to clay. Spectral measurements on low-ash (< 2 %) humic acids showed a positive correlation between extinction coefficient at 280 nm (E280) and C:H ratio, and negative correlations between E280 and percent of hydrolyzable C and N. The E4:E6 ratio was related to molecular weight, as determined by agar gel filtration, increasing with decrease in molecular weight.
Keywords: organic heteropolymers; soil organic matter; extraction-fractionation method; humus